Reconceptualisation of State Financial Losses to Prevent Misuse of Village Funds - Muti'ah, Dewi; Habibullah, Abd. Wachid; Djunarto, Yusaq; Cahyono, Luthfi Basith Eko (Faculty of Law Universitas Trunojoyo Madura, 2025)
Village Funds are funds provided to villages that originate from central and local government financial allocations received by districts/cities. The numerous cases of misuse of village funds in Indonesia led to the implementation of Law No. 20 of 2001, amending Law No. 31 of 1999 on the Eradication of Corruption Offences. This serves as the basis for classifying financial losses to the state resulting from the misuse of funds as acts of corruption. All village heads who misuse village funds can be categorised as committing acts of corruption. In fact, not all misuse of village funds is for personal gain, but rather to improve the financial condition of the village, Village-Owned Enterprises (BUMDes), and so on. The purpose of this study is to identify the characteristics of village fund embezzlement that constitute criminal acts of corruption. This study contributes to the development of criminal law science, particularly in relation to the elements of village fund embezzlement that constitute criminal acts of corruption. The research method used is normative legal research with a conceptual approach. The conclusion drawn from this study is that not all cases of embezzlement of village funds involve elements of financial loss to the state. Therefore, not all are categorised as criminal acts of corruption. The recommendation from this study is for the government to formulate policies for managing village funds, particularly regarding elements of embezzlement that constitute criminal acts of corruption or financial loss to the state.